Mineralogy of the Yamato diogenites as possible pieces of a single fall - Takeda, Hiroshi; Mori, Hiroshi; Yanai, Keizo (1981)
P(論文) Among 30 diogenites recovered from the Yamato meteorite field by the JARE parties, 29 meteorites totaling 6775.8g have a granoblastic texture distinct from known diogenites. We have proposed on the basis of their mineralogy that we are dealing with pieces of a single fall. In order to clarify their identity, we have reexamined thin sections of Yamato-74013,-74097,-74136 with optical, electron optical (TEM) and microprobe techniques. The meteorites are composed of fine-grained orthopyroxenes surrounded by coarse-grained areas and of chromites up to 5mm in diameter. Finer-grained portions with a haze of tiny inclusions of troilite and metallic iron show a subtle parallel structure that transects the granularity. The structure can be interpreted to be decorated with linear features produced by a shock event. The TEM observation of clear orthopyroxenes in coarser-grained areas (0.4-3.0mm) shows stacking faults parallel to (100), which are thought to have been produced by weak shock effects when the meteorite mass was formed. Neither exsolution nor dislocation indicating low strain-rate deformation has been observed. The rims of the large clear orthopyroxenes are richer in Ca and Fe than the other portions. In interstices of the coarsest portion, there are found graphic intergrowth of plagioclase and a silica mineral, and coarse-grained troilite. The characteristic texture of the Yamato diogenites may have been formed by recrystallization of a few very large crystals by heavy shock processes, and subsequent thermal annealing. Coarse-grained areas may indicate intergranular melting and recrystallization. Because the coarsest portions with rare-earth-element-rich plagioclase are distributed over intervals of a few cm, the differences found in separate masses may be attributed to the heterogeneity of sampling. departmental bulletin paper